"If Nobody Gives a Shit, is it Really News?": Changing standards of news production in a learning newsroom. Issue 1 (2nd January 2017) - Ross, Amy A.
Abstract : While a growing body of academic research explores the evolution of production practices within formal news organizations, much less attention is paid to how journalism schools are addressing the demands of the profession in the twenty-first century. Strains on the traditional routines, practices and unwritten rules of news production challenge those involved in professional development to rethink the standards and skills they prioritize as they transmit knowledge to the next generation of news workers. This paper explores some of these changes in a "learning newsroom" at one of the top journalism schools of the United States. The research is based on both qualitative and quantitative methods, including over 200 hours of ethnographic fieldwork conducted between January and June 2015, interviews with journalism graduate students and faculty members, content analyses of the articles published on the news organization's website, and an online survey. I focus on the recent shift within my fieldsite from a "learning newsroom" framework to a "Content Lab" alternative envisioned as preparation for graduate students in journalism for a radically different media ecosystem than that which existed in the past. The professionalization process within the Content Lab reflects the eroding boundaries of the institution of journalism. Three interrelated trends stand out in this context: a shift in the educational emphasis from story content to story form; increasingly flexible professional standards concerning what qualifies as news, resulting from the greater emphasis on the audience; and a growing horizontality in the educational process.